Endogenous endophthalmitis and multifocal brain abscess—An interesting case - Aman Mishra (Wiley, 2021)
Abstract We present an unusual case that staphylococcal brain abscess can present in an immunocompetent with endogenous endophthalmitis secondary to a septic foci and early prevention of dissemination with appropriate management to prevent its complications.